PEMBUATAN ARANG AKTIF DARI TEMPURUNG KELAPA DAN APLIKASINYA UNTUK PENGOLAHAN LIMBAH CAIR TAHU TEMPE - Septiani Mangiwa; Ilham Salim; Agnes Eri Maryuni (JURNAL PENGABDIAN PAPUA, 2020)
Industry of tofu and tempe continues to grow in the city of Jayapura. In the Kali Acai area there are at least four tofu and tempe processing plants. In its processing, the industry also produces by by side products in the form of solid and liquid waste. The lack of knowledge and the high cost of liquid waste processing equipment make the factory managers generally immediately dispose of the liquid waste to Kali Acai without processing it first. This can cause the waters of Kali Acai and the surrounding environment to become contaminated. To overcome this problem, socialization and training for managers and employees of the tofu and tempe factory were conducted at Kali Acai times, especially the Ojolali tofu tempe industry about processing liquid waste in a simple way by utilizing coconut shells so that disposed liquid waste is safer and environmentally friendly. The stages of activities carried out included: location surveys and partner selection, preparation of tools and materials, implementation of activities, evaluation and reporting. The implementation of the activity consisted of delivering material, making activated charcoal and processing wastewater using activated charcoal for. Activated charcoal is made from coconut shell with a closed system while the active charcoal application for processing wastewater uses an adsorption technique. The evaluation was carried out through questionnaires for the participants. The results of the activity showed that activated charcoal was able to adsorb color and acid from liquid waste. This is indicated by the change in color from cloudy white to be rather clear and able to increase pH from 5,04 to 7,45 so that it is safer for the environment. In general, the implementation of service activities went smoothly and successfully which was demonstrated through the enthusiasm of the participants and the results of the questionnaire analysis which was filled out by the participants. Keywords: activated charcoal, coconut shell, liquid waste treatment, tofu and tempe waste